Grant support and exporting activity - Holger Görg; Michael Henry; Eric Strobl (Centre for Economic Policy Research (CEPR), 2007)
This paper investigates whether government support can act to increase exporting activity. We use a uniquely rich data set on Irish manufacturing plants and employ an empirical strategy that combines a non-parametric matching procedure with a difference-in-differences estimator in order to deal with the potential selection problem inherent in the analysis. Our results suggest that if grants are large enough they can encourage already exporting firms to compete more effectively on the international market. However, there is little evidence that grants encourage non-exporters to start exporting.
Keywords: F2; H2; L2; O3; 380; Exportsubvention; Wirtschaftspolitische Wirkungsanalyse; Exporthandel; Irland